In vitro and in vivo elucidation of the role of miRNAS in the apoptotic properties of BCL-XLsilenced human lung adenocarcinoma cells / Norahayu Othman - Norahayu , Othman (2017)
Anti-apoptotic BCL-XL is frequently overexpressed in non-small cell lung cancer, leading to inhibition of apoptosis and poor prognosis. MicroRNAs play a role in regulating apoptosis and cell survival during tumourigenesis, with cancer cells showing perturbed expression of miRNAs. The aim of this study was to determine the biological effects of miRNA dysregulation on non-small cell lung cancer, and the molecular mechanisms by which apoptosis is regulated. Overexpression and knockdown studies were performed via transfection of miRNA mimics and inhibitors and cell death was detected using the annexin V-FITC detection kit and caspase 3/7 activity assay. Cell cycle analysis was also performed to determine the role candidate miRNAs play in cell growth. Results indicated that overexpression of miR-608 and down-regulation of miR- 361-5p induced cell death in A549 and SK-LU-1 cells. Gene target prediction analysis implicated various signaling pathways as targets of BCL-XL induced miRNA alterations. Luciferase reporter assay identified AKT2 and SMAD2 as direct targets of miR-608 and miR-361-5p, respectively, and suppression of its protein levels were validated using Western blot. To elucidate the role and importance of these miRNAs in vivo, labeled tumour cells were injected into the yolk sac of zebrafish embryos and immunostained using monoclonal antibodies to detect the cleaved, active form of caspase 3. In conclusion, BCL-XL silencing in A549 and SK-LU-1 cells leads to the occurrence of apoptosis through the dysregulation of miR-608 and miR-361-5p, thus providing a platform for anti-sense gene therapy whereby miRNA expression can be exploited to increase the apoptotic properties in lung adenocarcinoma cells.